The measurement of thermodynamic performance in cryogenic two-phase turbo-expander. (September 2015) - Niu, Lu; Hou, Yu; Sun, Wan; Chen, Shuangtao
Highlights: Liquid fraction in cryogenic turbo-expander is measured by a thermal method. Five different wetness conditions are tested in turbo-expander. Thermodynamic performance of two-phase expansion is evaluated by Baumann rule. Wetness loss is higher than predication especially in low wetness test case. Abstract: Liquid fraction measurement in cryogenic two-phase flow is a complex issue, especially for an industrial cryogenic system. In this paper, a simple thermal method is proposed for measuring the liquid fraction in cryogenic two-phase turbo-expander by an electric heating unit in experimental study. The liquid fraction of the cryogenic two-phase flow is determined through the heat balance built at the outlet of the turbo-expander (inlet of heating unit) and the outlet of the heating unit. Liquid fractions from 1.16% to 5.02% are obtained from five two-phase expansion cases. Under the same turbo-expander inlet pressure and rotating speed, five superheated expansion cases are tested to evaluate the wetness loss in two-phase expansion. The results show that the proposed method is successful in measuring the liquid fraction of cryogenic two-phase expansion for turbo-expander in an industrial air separation plant. The experimental isentropic efficiency ratio and the tested Baumann factor decrease with the increasing mean wetness. Based on prediction of Baumann rule, the cryogenic turbo-expander with low liquid fraction in two-phase expansion cases suffers from more severe wetness loss than that with the higher liquid fraction.